2023
DOI: 10.1037/rev0000391
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rhythms of the predictive mind.

Abstract: Respiratory rhythms sustain biological life, governing the homeostatic exchange of oxygen and carbon dioxide. Until recently, however, the influence of breathing on the brain has largely been overlooked. Yet new evidence demonstrates that the act of breathing exerts a substantive, rhythmic influence on perception, emotion, and cognition, largely through the direct modulation of neural oscillations. Here, we synthesize these findings to motivate a new predictive coding model of respiratory brain coupling, in wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 152 publications
0
31
0
Order By: Relevance
“… Perl et al, 2019 showed the alignment of self-initiated cognitive tests with the beginning of the inspiratory phase, and recent work by Kluger et al, 2021 has shown respiration-locked performance in a near-threshold spatial detection task. In this context, Allen et al, 2022 have proposed a predictive coding interpretation of respiratory cycle effects where breathing rhythmically modulates neural gain, which in turn optimizes cognitive and affective processing.…”
Section: Discussionmentioning
confidence: 99%
“… Perl et al, 2019 showed the alignment of self-initiated cognitive tests with the beginning of the inspiratory phase, and recent work by Kluger et al, 2021 has shown respiration-locked performance in a near-threshold spatial detection task. In this context, Allen et al, 2022 have proposed a predictive coding interpretation of respiratory cycle effects where breathing rhythmically modulates neural gain, which in turn optimizes cognitive and affective processing.…”
Section: Discussionmentioning
confidence: 99%
“…It generates rhythmic activity basically around 0.16 Hz and respiratory oscillations at the same frequency (ratio 1:1) or the double frequency (ratio 1:2). Note, these upwards coupling may www.nature.com/scientificreports/ suggest another possible pathway from the preBötzinger complex in the brainstem to the locus coeruleus and, moreover, via the medial thalamus and the olfactory bulb to the PFC and the limbic system 37,38 . Table 1 exhibits slow RRI waves (PD = 6.7 s + − 0.21) of various appearance between 2% and 54% in all subjects with high anxiety.…”
Section: Breathing Oscillations At ~ 032 Hz and Top-down Flowmentioning
confidence: 99%
“…Evidence has demonstrated that neural responses to heartbeats contribute to visual 14 , somatosensory 15 , auditory 16,17 , and self-perception [18][19][20] . Further, recent evidence has suggested that breathing is aligned with the perception of sensory inputs 21,22 , suggesting that it is involved in perceptual sensitivity modulation and, possibly, shaping neural dynamics 23,24 .…”
Section: Confounding Effects Of Heart Rate Breathing Rate and Frontal...mentioning
confidence: 99%